An Ecobehavioral Analysis of Child Academic Engagement: Implications for Preschool Children Not Responding to Instructional Intervention. (February 2018) - Greenwood, Charles R.; Beecher, Constance; Atwater, Jane; Petersen, Sarah; Schiefelbusch, Jean; Irvin, Dwight
A gap exists in the information needed to make intervention decisions with preschool children who are unresponsive to instructional intervention. Multi-Tiered System of Supports/Response to Intervention (MTSS/RTI) progress monitoring is helpful in indicating when an intervention change is needed but provides little information on what to change. Ecobehavioral observation data may provide this support through information on a child's academic and other behaviors, given the opportunity to learn. We sought to investigate this hypothesis and develop benchmarks for decision making. Teachers ( N = 39) and two representative age-cohorts of preschool children ( N = 117, 51% boys) were observed using an ecobehavioral, momentary time sample observation system (the Code for Interactive Recording of Children's Learning Environments [CIRCLE]). Results provided insights into the content and amount of academic instruction children received, the responsiveness of children to instruction, and how context/teacher and child behaviors relationships were moderated by children's level of Get Ready to Read (GRTR) literacy and Individualized Education Plan (IEP) status risk. Implications are discussed.